2004
DOI: 10.1002/ajh.20232
|View full text |Cite
|
Sign up to set email alerts
|

An unusual ocular manifestation in Fanconi anemia: Congenital glaucoma

Abstract: Fanconi anemia is an autosomal recessive disorder characterized by growth retardation along with many congenital abnormalities involving the eyes. We report herein two siblings with Fanconi anemia who also have bilateral congenital glaucoma. To the best of our knowledge, this is the first report of congenital glaucoma in patients with Fanconi anemia. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The changes in the crystalline lens in the present study seem to be more related in this study to the SCT treatment than to the actual disease as has been previously reported (Merri- Elgohary et al 2006). None of the patients had increased intraocular pressure or glaucomatous changes in the optic nerve and neither ischaemia nor retinal vascularization as previously reported (Aslan et al 2005;Bahar et al 2005;Yahia et al 2006). Optic nerve hypoplasia is defined as a reduced number of axons in the ONH that leads to a small optic disc.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The changes in the crystalline lens in the present study seem to be more related in this study to the SCT treatment than to the actual disease as has been previously reported (Merri- Elgohary et al 2006). None of the patients had increased intraocular pressure or glaucomatous changes in the optic nerve and neither ischaemia nor retinal vascularization as previously reported (Aslan et al 2005;Bahar et al 2005;Yahia et al 2006). Optic nerve hypoplasia is defined as a reduced number of axons in the ONH that leads to a small optic disc.…”
Section: Discussionsupporting
confidence: 81%
“…Isolated case reports have described congenital glaucoma (Aslan et al 2005), cataract (Elgohary et al 2006), uveal or optic disc vasculopathy (Yahia et al 2006;Jain et al 2007) and retinoblastoma (Gibbons et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular abnormalities have been reported in up to 38% of patients and include microcornea with or without microphthalmia,18 strabismus, epicanthal folds, ptosis, cataract,19, 20 increased crystalline lens thickness and phacomorphic glaucoma,21 congenital glaucoma22 and retinal vasculopathy leading to ischemia and retinal neovascularization 19, 23, 24…”
Section: Discussionmentioning
confidence: 99%
“…12 Endocrinopathies, including growth hormone insufficiency, hypothyroidism, glucose intolerance, hyperinsulinism, and/or overt diabetes mellitus, occur in 81% of patients. 4 Nonocular congenital anomalies occur in 65% to 75%, 13,14 with skeletal anomalies, most commonly short stature, radial ray reduction and thumb abnormalities, café-au-lait skin pigmentations, and renal malformations occurring in up to 70%. Less frequent abnormalities include hypogonadism; mental retardation; and gastrointestinal, cardiac, hearing, and central nervous system abnormalities.…”
mentioning
confidence: 99%